Creating Something out of Nothing: Food, Sex, and Housing in Havana’s Underground Economies - Thorne, Cory (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
While pervasive through much of Cuban society, underground economies take on special significance within the LGBTQI+ community. Not only must we engage in deep contextualization and seek vernacular theorization within everyday life, but we must also consider queer timelines – queer temporalities as part of any analysis while simultaneously abandoning Global North identity categories as they relate to Global South performances. This essay is part of a larger project – a critical queer ethnography of Cuban everyday life – however with a focus on the negotiations of ethics, relationships, and community as a means of survival for individuals who are largely invisible to broader society. Though erased, ignored, and hidden, these individuals share universal characteristics which we must not exoticize in relation to our own experiences: food, sex, and housing are fundamental elements to life, regardless of privilege or legality.